2012
DOI: 10.1002/jctb.3738
|View full text |Cite
|
Sign up to set email alerts
|

Fed‐batch fermentation of olive mill wastewaters for lipase production

Abstract: In the Mediterranean basin countries, huge amounts of olive mill wastewaters (OMW) are produced by the olive oil industry. It constitutes a serious environmental problem, nevertheless its composition turns OMW into a potential growth medium to lipolytic microorganisms. The aim of this work was to study lipase production as well as OMW degradation in fed-batch cultures of Candida cylindracea CBS 7869, Candida rugosa CBS 2275 and Yarrowia lipolytica W29 (ATCC 20460). Besides the improvement of lipase production,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In this work, the agro-industrial waste OMW (which composition is summarized in Table 1) was evaluated as an inducer of rhamnolipid production. Although the composition of OMW depends on several factors as previously explained, the results herein showed are in accordance with previous characterizations of OMW obtained from the same region (Amaral et al, 2012;Gonçalves et al, 2009Gonçalves et al, , 2012.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In this work, the agro-industrial waste OMW (which composition is summarized in Table 1) was evaluated as an inducer of rhamnolipid production. Although the composition of OMW depends on several factors as previously explained, the results herein showed are in accordance with previous characterizations of OMW obtained from the same region (Amaral et al, 2012;Gonçalves et al, 2009Gonçalves et al, , 2012.…”
Section: Resultssupporting
confidence: 93%
“…The concentration of total carbohydrates and protein in these residues were determined using the phenolsulfuric and Lowry methods, respectively (Dubois et al, 1956;Lowry et al, 1951). Furthermore, OMW was characterized in terms of pH, total solids, total phenols, total lipids and long-chain fatty acids composition, using methodologies described elsewhere (Amaral et al, 2012;Gonçalves et al, 2009Gonçalves et al, , 2012. Total solids were determined by oven drying (105°C) to constant weight.…”
Section: Agro-industrial Residuesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported that at neutral or alkaline pH, polyphenols transformed into phenolates, losing part of their antimicrobial activity and becoming a suitable carbon source for micro-organisms [10]. On the other hand, fed-batch systems used in the biotreatment of OMW are limited [13,14]. To our knowledge, however, a system for OMW biodegradation depending on the pH adjustment has not been reported yet.…”
Section: Biodegradation Of Omw By Free R Glutinismentioning
confidence: 96%
“…59 Other valorization strategies could utilize the residual oil in OMWW by turning it into a potential growth medium for lipolytic micro-organisms. 57,58 Gonçalves et al 62 verifi ed this strategy by studying the lipase production from Candida cylindracea, Candida rugosa and Yarrowia lipolytica. Besides the improvement of lipase production, COD and lipids were reduced by more than 50%.…”
Section: Other Valorized Productsmentioning
confidence: 99%